2019
DOI: 10.1080/16066359.2019.1629426
|View full text |Cite
|
Sign up to set email alerts
|

Long waves of consumption or a unique social generation? Exploring recent declines in youth drinking

Abstract: This is a repository copy of Long waves of consumption or a unique social generation? Exploring recent declines in youth drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 87 publications
(86 reference statements)
5
79
0
1
Order By: Relevance
“…Our results support findings in other studies, suggesting changes in the normative climate around drinking among young people, increased emphasis on academic achievement and a disciplined way of life, and a more health-oriented lifestyle as explanations for non-drinking [1,[7][8][9][10]. They also align with Kraus et al [10] who hypothesise that changes in the social position of alcohol are related to how its perceived negative effects do not fit with an increasingly healthoriented youth culture, and also to changes in technology, social norms and family relationships. As in a recent qualitative study from Sweden [19], our findings indicate that the cultural position of drinking may have changed among young adolescents, towards a situation where alcohol has less importance in peer networks [20] and where alcohol use is devalued [10].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results support findings in other studies, suggesting changes in the normative climate around drinking among young people, increased emphasis on academic achievement and a disciplined way of life, and a more health-oriented lifestyle as explanations for non-drinking [1,[7][8][9][10]. They also align with Kraus et al [10] who hypothesise that changes in the social position of alcohol are related to how its perceived negative effects do not fit with an increasingly healthoriented youth culture, and also to changes in technology, social norms and family relationships. As in a recent qualitative study from Sweden [19], our findings indicate that the cultural position of drinking may have changed among young adolescents, towards a situation where alcohol has less importance in peer networks [20] and where alcohol use is devalued [10].…”
Section: Discussionsupporting
confidence: 89%
“…Scholars have offered a number of possible explanations for the declining trend in alcohol use among younger adolescents. These include: better enforcement of the minimum legal age for alcohol purchase; changes in social norms related to drinking among young people and immigration from non-drinking cultures; a more competitive society with an emphasis on academic achievement and a disciplined way of life; a more health-oriented lifestyle; changes in parenting and parental norms; lower affordability and the rise of internet-based technologies [1,[7][8][9][10]. There are still rather few empirical studies assessing whether, or to what extent, one or more of these explanations are valid [1,9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that increased parental knowledge and stricter alcohol-specific parenting have contributed to the downward drinking trend [6,[11][12][13]. Kraus et al [7] suggested that parents have also become less likely to drink in front of their adolescent children. However, we found no empirical support for this suggestion, as perceived parental drinking frequency did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a decrease in adolescents' involvement in hazardous driving, unsafe sex, crime and delinquency has been observed, which may reflect wide-ranging cultural and normative shifts. In the USA, the decline in such risky and deviant behaviours preceded the drop in drinking to intoxication [7,10]. On the other hand, it has been suggested that the decline in drinking to some extent reflects that cannabis had substituted alcohol, but the few studies that addressed the issue, provided no evidence in support of this suggestion [6].…”
Section: Introductionmentioning
confidence: 99%